Using Character Education Forms and Values of Folklores in Brebes Regency as the Old Literature Learning Materials - Umi Ana Setiani; Sukirno Sukirno; M. Riyanton; Mustasyfa Thabib Kariadi (Faculty of Humanities, Universitas Jenderal Soedirman, 2021)
This research aimed at analyzing the character education forms and values contained in the folklores of Brebes Regency including their relevance for the old literature learning materials at higher education institutions. This research used a qualitative method with an ethnographic approach. The data were collected using an observational study, in-depth interview, note-taking, and documentation. The results show that the folklores in Brebes Regency are in the form of legends and myths. Besides, the folklores of Brebes Regency also contain 13 educational character values consisting of religiousness, hard-working, nationalism and patriotism, appreciating achievements, friendly/communicative, environmental awareness, responsibility, curiosity, discipline, democracy, honesty, tolerance, and social awareness value. Thus, the folklores of Brebes Regency are considered relevant to use as the old literature learning materials at higher education institutions since they are not only appropriate and functional in providing adequate experiences for the students but also containing noble values to follow.